Dental Fluorosis and Its Associated Factors Amongst Libyan Schoolchildren - Arheiam Arheiam; Aisha Aloshiby; Amal Gaber; Sarah Fakron (Elsevier, 2022)
Background: Little is known about dental fluorosis (DF) in Benghazi, Libya, where the public water supply is naturally fluoridated. Objective: The study aims to investigate the distribution of DF and its related risk factors and impact on oral health-related quality of life (OHRQoL) and the association between DF and caries amongst Libyan school children. Methods: A cross-sectional survey was carried out amongst 12-year-old schoolchildren in the city of Benghazi. Dean's and decayed, missing, and filled surfaces (DMF) indices were used to assess the severity of DF and dental caries. In addition, a self-administered questionnaire was used to collect sociodemographic and behavioural information and OHRQoL using the Child Oral Health Impact Profile-Short Version 19 (COHIP-SF19). Results: Out of 1125 children who participated in the study, 15%, 7.8%, 2.2%, and 0.4% of participants were coded as having questionable, mild, moderate, and severe DF, respectively. Children enrolled in private schools were less likely to have DF (odds ratio, 0.55; 95% confidence interval, 0.35-0.83; P = .007). Moderate-severe DF was associated with more decayed surfaces and DMF scores and low scores for COHIP-SF19 and its socioemotional well-being subscale. Conclusions: The data demonstrate that rates of DF are relatively low in naturally fluoridated areas in Libya. DF amongst Libyan schoolchildren was associated with social disparities, higher caries rates, and negative impacts on OHRQoL.